Digital hoarding behaviours: Measurement and evaluation. (July 2019) - Neave, Nick; Briggs, Pam; McKellar, Kerry; Sillence, Elizabeth
Abstract: The social and psychological characteristics of individuals who hoard physical items are quite well understood, however very little is known about the psychological characteristics of those who hoard digital items and the kinds of material they hoard. In this study, we designed a new questionnaire (Digital Behaviours Questionnaire: DBQ) comprising 2 sections: the Digital Hoarding Questionnaire (DHQ) assessing two key components of physical hoarding (accumulation and difficulty discarding); and the second measuring the extent of digital hoarding in the workplace (Digital Behaviours in the Workplace Questionnaire: DBWQ). In an initial study comprising 424 adults we established the psychometric properties of the questionnaires. In a second study, we presented revised versions of the questionnaires to a new sample of 203 adults, and confirmed their validity and reliability. Both samples revealed that digital hoarding was common (with emails being the most commonly hoarded items) and that hoarding behaviours at work could be predicted by the 10 item DHQ. Digital hoarding was significantly higher in employees who identified as having 'data protection responsibilities', suggesting that the problem may be influenced by working practices. In sum, we have validated a new psychometric measure to assess digital hoarding, documented some of its psychological characteristics, and shown that it can predict digital hoarding in the workplace. Highlights: We designed a new questionnaire to measure digital hoarding behaviours. In two large samples we validated the questionnaire. Digital hoarding is common and partly reflects the job demands associated with data protection. Digital hoarding is associated with characteristics of physical hoarding.